Gestational anemia and maternal antenatal and postpartum psychological distress in a prospective FinnBrain Birth Cohort Study - Kemppinen Lotta; Mattila Mirjami; Ekholm Eeva; Huolila Linda; Pelto Juho; Karlsson Hasse; Mäkikallio Kaarin; Karlsson Linnea (BMC, 2025)
Background
Gestational anemia, most commonly caused by iron deficiency, may increase the risk of maternal anxiety and depression and have a potentially far-reaching impact on mother’s and newborn’s health. Several mechanisms, such as effects of iron deficiency on cerebral neurotransmitter metabolism, have been suggested. None of the earlier studies have assessed the association between gestational anemia and depression, anxiety and pregnancy-related anxiety simultaneously.
Methods
Women, participating in the FinnBrain Birth Cohort Study and attending maternity welfare clinics in Turku, whose hemoglobin (Hb) values during pregnancy were available were included in this study (n = 1273). The study group consisted of 301 women with Hb levels < 11.0 g/dL at any time during pregnancy, and 972 women with Hb ≥ 11.0 g/dL were included in the control group. Symptoms of depression, anxiety, and pregnancy-related anxiety were assessed using the Edinburgh Postnatal Depression Scale (EPDS), Symptom Checklist-90 (SCL), and Pregnancy-Related Anxiety Questionnaire (PRAQ) questionnaires at 14, 24, and 34 gestational weeks, and EPDS and SCL were also performed 3 and 6 months postpartum.
Results
Gestational anemia was not associated with an increased risk of depression either prenatally or postpartum when the analyses were adjusted for maternal age at birth, parity, smoking during pregnancy, maternal education, and gestational age. However, a weak connection was found between gestational anemia and prenatal anxiety in the early pregnancy. Furthermore, the analysis between women with Hb < 10.0 g/dL and those with Hb ≥ 10.0 g/dL showed an association between gestational anemia and anxiety in the late pregnancy, but otherwise no difference in psychological distress was found.
Conclusions
No evidence supporting the association between gestational anemia and antenatal or postpartum depression was found. However, a weak connection between gestational anemia and antenatal anxiety was observed. This finding needs further investigation to establish timing and investigate causality.